Becoming fathers, becoming caregivers: A qualitative exploration of intersectional influences shaping caregiving in an urban poor South Indian setting - Eunice Lobo; Joshua Jeong; Giridhara Rathnaiah Babu; Debarati Mukherjee; Onno C. P. van Schayck; Prashanth Nuggehalli Srinivas (PLoS ONE, 2025)
Background Caregiver engagement is crucial for early child development; however, research on paternal involvement remains limited, particularly in urban settings of the Global South. This exploratory study aimed to understand how fathers’ lived experiences and aspirations, along with systemic inequities, shape their parenting practices in urban poor settings in Bangalore, South India. Methods Ten fathers of children aged 4–6 years from low socio-economic backgrounds in the MAASTHI birth cohort were purposively selected for in-depth interviews, conducted using a pre-tested topic guide in Hindi and Kannada . All interviews were transcribed, translated, and analysed using a thematic analysis approach. Results Fathers prioritized their children’s education and safety, often viewing financial provision as their primary role due to ingrained gender norms and economic hardship. Most worked long hours in informal employment, thereby limiting their participation in daily caregiving, which was typically handled by their mothers. Fathers’ own childhood experiences influenced their parenting, with those who experienced adversity often aiming to break intergenerational cycles by being more emotionally present and supportive. While structural barriers limited involvement, many fathers expressed a strong desire to be more engaged, thereby challenging traditional roles. Safety concerns in their neighbourhoods further shaped protective parenting practices. Despite these constraints, some fathers reported that they preferred spending time with their families and participated in co-parenting through shared decision-making and engaging in play. Conclusion This study highlights the intersectionality between gender, socio-economic status, and intergenerational adversity in shaping fathering practices. To promote inclusive caregiving, early childhood programmes must actively include fathers and address both individual and structural barriers that constrain their involvement.